Big Bird Plots: Benchmarking Neotropical Bird Communities to Address Questions in Ecology and Conservation in an Era of Rapid Change - Robinson, W. Douglas; Errichetti, Dan; Pollock, Henry S.; Martinez, Ari; Stouffer, Philip C; Shen, Fang-Yu; Blake, John G. (Frontiers in Ecology and Evolution, 2021)
Extensive networks of large study plots have the potential to transform knowledge by establishing benchmarks of avian community dynamics through time and across geographical space. In the Neotropics, the global hotspot of avian diversity, published inventories exist for only six 100-ha plots, all of which are located in lowland forests and five of which are located in northern South America. We review the most important lessons learned about Neotropical forest bird communities from those big bird plots and explore opportunities for creating a more extensive network of additional plots to address questions in ecology and conservation, following the model of the existing ForestGEO network of tree plots. Scholarly impact of the big bird plot papers has been extensive, with the papers accumulating nearly 1,500 citations, particularly on topics of tropical ecology, avian conservation and community organization. Abundance patterns varied substantially between the five South American plots and the Central American plot, suggesting different community structuring mechanisms are at work and that a broader geographic sampling is needed. Total bird abundance in Panama, dominated by small insectivores, was double that of Amazonia and the Guianan plateau, which were dominated by large granivores and frugivores. The most common species in Panama were three times more abundant than those in Amazonia, whereas overall richness was 1.5 times greater in Amazonia. Despite these differences in community structure, biomass distributions were remarkably similar across the plots. More plots are needed to increase generalizability of results and reveal the texture of geographic variation. We propose fruitful avenues of future research based on our current synthesis of the big bird plots. In particular, collaboration with the large network of ForestGEO forest dynamics plots would improve understanding of linkages between plant and bird diversity and track change through time. Careful quantification of bird survey effort, recording of exact locations of survey routes or stations, and archiving detailed metadata will greatly enhance the value of benchmark data for future repeat surveys of the existing plots and initial surveys of newly established plots.